microRNA122-regulated transgene expression increases specificity of cardiac gene transfer upon intravenous delivery of AAV9 vectors - Geisler, Anja; Jungmann, Andreas; Kurreck, Jens; Poller, Wolfgang; Katus, Hugo; Vetter, Roland; Fechner, Henry; Müller, Oliver J. (Gene therapy, 2011)
Adeno-associated virus (AAV) vectors with capsids of AAV serotype 9 enable an efficient transduction of the heart upon intravenous injection of adult mice but also transduce the liver. The aim of this study was to improve specificity of AAV9 vector-mediated cardiac gene transfer by microRNA (miR)-dependent control of transgene expression. We constructed plasmids and AAV vectors containing target sites (TSs) of liver-specific miR122, miR192 and miR148a in the 3′ untranslated region (3′UTR) of a luciferase expression cassette. Luciferase expression was efficiently suppressed in liver cell lines expressing high levels of the corresponding miRs, whereas luciferase expression was unaffected in cardiac myocytes. Intravenous injections of AAV9 vectors bearing three repeats of miR122 TS in the 3′UTR of an enhanced green fluorescent expression (EGFP) expression cassette resulted in the absence of EGFP expression in the liver of adult mice, whereas the control vectors without miR TS displayed significant hepatic EGFP expression. EGFP expression levels in the heart, however, were comparable between miR122-regulated and control vectors. The liver-specific de-targeting in vivo using miR122 was even more efficient than transcriptional targeting with a cardiac cytomegalovirus (CMV)-enhanced myosin light chain (MLC) promoter. These data indicate that miR-regulated targeting is a powerful new tool to further improve cardiospecificity of AAV9 vectors.
Gesehen am 18.10.2023
Online veröffentlicht am 04. November 2010